Methylation polymorphism influences practice effects in children during attention tasks. Issue 2 (3rd April 2017) - Voelker, Pascale; Sheese, Brad E.; Rothbart, Mary K.; Posner, Michael I.
ABSTRACT: Epigenetic mechanisms mediate the influence of experience on gene expression. Methylation is a principal method for inducing epigenetic effects on DNA. In this paper, we examine alleles of the methylenetetrahydrofolate reductase (MTHFR) gene that vary enzyme activity, altering the availability of the methyl donor and thus changing the efficiency of methylation. We hypothesized that alleles of the MTHFR gene would influence behavior in an attention-related task in conjunction with genes known to influence attention. We found that seven-year-old children homozygous for the C allele of MTHFR in interaction with the catechol O -methyltransferase (COMT) gene showed greater improvement in overall reaction time (RT) and in conflict resolution with practice on the Attention Network Test (ANT). This finding indicates that methylation may operate on or through genes that influence executive network operation. However, MTHFR T allele carriers showed faster overall RT and conflict resolution. Some children showed an initial improvement in ANT RT followed by a decline in performance, and we found that alleles of the dopamine beta-hydroxylase (DBH) gene were related to this performance decline. These results suggest a genetic dissociation between improvement while learning a skill and reduction in performance with continued practice.